Water use efficiency and yield of cowpea and nutrient loss in lysimeter experiment under varying water table depth, irrigation schedules and irrigation method (SAARC Journal of Agriculture, 2017)
Lysimeter experiment was conducted at Govind Ballabh Pant University of Agriculture & Technology, Pantnagar during summer season 2013 to study the effect of irrigation schedules and methods on yield, nutrient uptake and water use efficiency of cowpea as well as nutrient loss from silty clay loam soil under fluctuating water table conditions. The experiment was laid out in factorial randomized block design having three irrigation schedules at IW/CPE ratio of 0.3. 0.2 and 0.15 with two irrigation methods (flood and sprinkler) and at 30±1.5, 60±1.5 and 90±1.5 cm water tables replicated thrice. Maximum root length (129.4 cm) and root length density (0.395 cm/cm3) were obtained when irrigation was scheduled at IW: CPE 0.3 associated with 30±1.5 cm water table depth using sprinkler method. Increase in water table depth and IW: CPE ratio decreased water use efficiency where IW: CPE 0.3 produced highest grain yield (1411.6 kg ha-1) with the WUE of 1.15 kg ha mm-1. Significant nutrients uptake response was observed owing to variation in water table depth, irrigation schedules and methods. Analysis of lysimeter leached water showed that with deep drainage and more IW:CPE, leaching losses of N,P and K were more however water applied through sprinkler saved 20.1, 53.7 and 24.4% N, P and K, respectively, over flooded method. Irrigation given at IW: CPE 0.3 through sprinkler form at 60±1.5 cm water table depth favours the higher grain yield and nutrient uptake by crop whereas flooded irrigation with deep water table condition accelerated nutrient leaching.SAARC J. Agri., 14(2): 46-55 (2016)